2014
DOI: 10.1007/s10157-014-0992-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular remodeling during long-term nocturnal home hemodialysis

Abstract: BackgroundCardiovascular disease is the leading cause of morbidity and mortality in patients with kidney failure. Nocturnal home hemodialysis (NHD) is a form of kidney replacement therapy whereby hemodialysis is performed for at least 6-h overnight, at least 4 days per week. Little is known about the effects of NHD on cardiovascular remodeling as assessed by transthoracic echocardiography (TTE) and cardiac magnetic resonance imaging (CMR).ObjectivesThe primary objective of the study was to determine the long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Moreover, our results show that LVH regression or prevention may be achieved in a substantial proportion of patients with intensive more frequent hemodialysis, regardless of renal replacement therapy modality prior to initiation. These results are also consistent with other studies demonstrating improved LVM with intensive hemodialysis [16,[20][21][22] . This is in contrast to studies in peritoneal dialysis or conventional hemodialysis, which have shown that LVH develops and progresses in the majority of patients with time [4,14] .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, our results show that LVH regression or prevention may be achieved in a substantial proportion of patients with intensive more frequent hemodialysis, regardless of renal replacement therapy modality prior to initiation. These results are also consistent with other studies demonstrating improved LVM with intensive hemodialysis [16,[20][21][22] . This is in contrast to studies in peritoneal dialysis or conventional hemodialysis, which have shown that LVH develops and progresses in the majority of patients with time [4,14] .…”
Section: Discussionsupporting
confidence: 83%
“…Sixteen patients (18.4%) in the regressor group and 19 patients Studies in conventional hemodialysis and peritoneal dialysis have shown that LVH progresses with time in most patients [4,14,15] . In contrast, there has been many studies in recent years demonstrating that frequent hemodialysis (short-daily or long-nocturnal) leads to LVH regression along with improvements in blood pressure control, abnormalities of mineral metabolism, sleep quality and quality of life [16][17][18][19][20][21] . In the Frequent Hemodialysis Network Daily Trial, 245 patients were randomized to 6X/week (short-daily or nocturnal) or 3X/week hemodialysis [22] .…”
Section: Abstract Intensive Hemodialysis · Home Hemodialysis · Left mentioning
confidence: 98%
“…There was also a significant reduction in both left and right atrial volumes as well as in right ventricular (RV) mass index over 1 year of followup. 25 Diastolic dysfunction also improved from a baseline grade of 3.4 to 1.2 at 1 year of follow-up. In contrast, an analysis of the FHN Nocturnal Trial 26 revealed that there was no significant difference in LV or RV volume, or ejection fractions, with a good residual renal function for this cohort postulated to be one of the reasons contributing to this difference.…”
Section: Cardiacmentioning
confidence: 83%
“…58 The live birth rate in the Canadian cohort (86.4%) was significantly higher than the American cohort (61.4%, P=0.03). The median duration of pregnancy in the more intensely dialyzed Toronto cohort was 36 weeks (interquartile range 32-37) compared to 27 weeks (interquartile range [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] in the American cohort.…”
Section: Pregnancymentioning
confidence: 99%
“…Countries with long distances between the hospital and the patient's home, such as Canada, New Zealand, Australia, and the US, have well‐developed HHD programs . Although distance is not a problem in Spain—patients rarely live more than 10 km from a hospital—two patients moved to a larger city in order to be nearer to a hospital.…”
Section: Discussionmentioning
confidence: 99%